LEARNING WHILE RELAXING: PHYSICAL STUDENTS’ EXPERIENCES OF LEARNING ENGLISH VOCABULARY BY SONGS - Fadli, Zen; Sembiring, Heri Masmur; Isdianto, M. Eko; Andayani, Widya (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
The objective of this study was to investigate the perspectives of students on the utilization of songs as a medium for acquiring English vocabulary. The primary approach employed for data collecting was conducting WhatsApp chats. The study encompassed a sample size of 10 participants who exhibited a range of linguistic backgrounds and possessed differing degrees of competency in the English language. Thematic analysis was employed to assess the data generated from interviews done through WhatsApp chat. The results of this study indicate that students hold a favorable impression of the utilization of songs as a pedagogical method for enhancing their acquisition of English vocabulary. The participants had a positive reception towards the learning process, indicating an enhanced motivation to acquire knowledge and a heightened level of engagement with the English language when incorporating music. The participants additionally said that songs facilitated the development of crucial listening skills, the acquisition of novel terminology, and enhanced their ability to retain information. Furthermore, the research revealed that the utilization of songs facilitated rapid advancement among students, hence enhancing their self-assurance in the acquisition of English vocabulary. Moreover, the aforementioned findings underscore the potential advantages of employing technology for data collection purposes, as well as the significance of taking into account the viewpoints of students when formulating efficacious pedagogical approaches.